Factors Affecting Maize Yield in Machakos County - Velesi, David S. (Machakos University, 2018)
Maize is the main staple crop for many people in Kenya. It is a high yielding cereal grown almost in all parts of the country mainly under rain fed environmental conditions. However, despite the fact that maize is the main subsistence crop there has been structural maize deficit in Kenya which has pushed the prices of maize and maize products up beyond affordable level of many households leading to food insecurity. This forced the country to import maize from other countries to cover the shortage and also provide subsidized maize flour at ksh 90 per 2kg packet. There are various factors that affect maize yield and therefore research was aimed at assessing the factors that affect maize yield in Machakos County. The research targeted mainly small-scale and large-scale farmers in Machakos County. The study sought to achieve the following objectives: To examine the maize production and yield trends for the last 10 years in Machakos County. To find out the factors that constrain realization of high maize yield in the county. The research was conducted between July and November 2017 and involved random selection of farmers by visiting them and receiving direct responses from them as they answered the questionnaires. Through the field visits; The questionnaires, interviews and field observations provided the study with primary data. Secondary data was obtained from the Ministry of Agriculture (MOA), National Cereals and Produce Board (NCPB) in Machakos and Kenya agricultural research Centre (KARLO) in Machakos. After data collection, the research findings were analyzed using graphs, frequency tables and percentages and also in regression to establish the relationship between maize yield and the explanatory variables. The research found that maize yield in Machakos county is affected negatively by prolonged droughts and shortage of rainfall due to weather variability, poor soils most of which are very acidic and others are highly alkaline (MOA 2014), lack of agricultural advisory services, lack of essential inputs. The research shall greatly benefit the farming communities comprising of both small scale and large-scale maize producers and also traders of either maize products or farm inputs. The study shall help the farmers to identify the relationship between output and variables that affect the yield they get from their farming activities.
Keywords: Maize yield; Yield trends; Food policy; Food security; Small and large Scale farmers